2023
DOI: 10.1242/dev.200477
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic translation initiation factor eIF4E-5 is required for spermiogenesis inDrosophila melanogaster

Abstract: Drosophila sperm development is characterized by extensive post-transcriptional regulation whereby thousands of transcripts are preserved for translation during later stages. A key step in translation initiation is the binding of eukaryotic initiation factor 4E (eIF4E) to the 5’ mRNA cap. In addition to canonical eIF4E-1, Drosophila has multiple eIF4E paralogs, including four (eIF4E-3, -4, -5, and -7) that are highly expressed in the testis. Among these, only eIF4E-3 has been characterized genetically. Here, u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…The hybridization chain reaction (HCR) FISH protocol used 56 was optimized for use with Drosophila testes with the following modifications. In most cases, testes were cut in half while in PBS, then fixed on polylysine-coated slides as previously described 57 . When not used immediately, sample-containing slides were stored at 4 °C in 95% ethanol and, prior to use, rinsed 3× for 5 min in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…The hybridization chain reaction (HCR) FISH protocol used 56 was optimized for use with Drosophila testes with the following modifications. In most cases, testes were cut in half while in PBS, then fixed on polylysine-coated slides as previously described 57 . When not used immediately, sample-containing slides were stored at 4 °C in 95% ethanol and, prior to use, rinsed 3× for 5 min in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…eIF4E-3 and eIF4E-5 proteins are specifically expressed in the testis and, together with eIF4E-1, play crucial roles in different processes to produce mature sperm. Indeed, eIF4E-1, eIF4E-3, and eIF4E-5 proteins are essential for spermatogenesis, and loss-of-function or mutation analyses showed that males lacking eIF4E-1, eIF4E-3, or eIF4E-5 are sterile (Ghosh & Lasko, 2015;Hern andez et al, 2012;Shao et al, 2023) (Fig. 6C).…”
Section: Eif4e In Drosophilamentioning
confidence: 98%
“…eIF4E‐3 is expressed in germline cells from the primary spermatocyte stage to the early differentiating spermatids immediately before the onset of spermiogenesis, and is required for cytokinesis and meiotic chromosome segregation and sperm individualization (Hernández et al ., 2012). eIF4E‐5 localises to the distal ends of elongated spermatid cysts and is required for post‐meiotic stages, including spermatid cyst polarisation and sperm individualization (Shao et al ., 2023).…”
Section: Eif4e In Drosophilamentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, post-transcriptional regulation plays a pivotal role in the overall coordination of gene expression 31 . It is important to highlight that the maturation of insect sperm involves extensive posttranscriptional regulation, whereby a signi cant number of transcripts are preserved for translation at a later stage 32 . In recent years, long non-coding RNAs (lncRNAs) have emerged as crucial factors in posttranscriptional regulatio 33,34 .…”
Section: Introductionmentioning
confidence: 99%